Program Intenzivnega monitoringa gozdov v Sloveniji (2004–2024) - Simončič, Primož (Gozdarski vestnik, 2024)
In 2024, we mark 20 years of the Intensive Forest Monitoring Program activities in Slovenia, a part of the international ICP Forests program and the UN ECE CLTRAP convention. The main goal of the activities is to monitor the impacts of air pollution and other factors on the forest ecosystems. We perform diverse monitoring and measurements and tree conditions following the internationally harmonized protocols on plots of ten hectares in Slovenia. The annual reports on the condition of forests are available to the public on the web pages of the Slovenian Forestry Institute and Institute for Forest Ecosystems Thüngen in Germany. The results of intensive forest monitoring are important for understanding the response of the trees to environmental changes, extreme occurrences, diseases, and other factors. They form a part of the research activity and understanding of forest development on the selected objects.
Keywords: ICP Forests; Intensive Forest Monitoring program; Program intenzivni monitoring gozdov; Slovenia; Slovenija